2021
DOI: 10.1183/23120541.00812-2020
|View full text |Cite
|
Sign up to set email alerts
|

“It's like being on a roller coaster”: the burden of caring for people with severe asthma

Abstract: IntroductionFamily carers and significant others play a fundamental role in the well-being of people with severe asthma. This study aimed to investigate the challenges faced by family carers/significant others of people with severe asthma, to understand if there is an unmet need and to explore coping strategies.MethodsCarers of people with severe asthma were invited to participate in a face-to-face or telephone interview. Semi-structured interviews were conducted until reaching data saturation of themes. The 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…These results are comparable to those reported by Farquhar et al, 37 highlighting COPD carer support needs. Our findings also showed that a higher proportion of severe asthma carers desired a better understanding of the nature of illness, consistent with the findings of Majellano et al 23 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are comparable to those reported by Farquhar et al, 37 highlighting COPD carer support needs. Our findings also showed that a higher proportion of severe asthma carers desired a better understanding of the nature of illness, consistent with the findings of Majellano et al 23 …”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this is the first study to evaluate QoL of severe asthma carers and indeed the first to compare the impacts in severe asthma compared to COPD. A previous study by the present authors evaluated the burden of caring for people with severe asthma using a qualitative descriptive methodology 23 . While this was the first study to report on severe asthma carer burden, the sample was small and only included one disease population.…”
Section: Discussionmentioning
confidence: 99%
“…This requires focusing on certain key traits that can be easily identified and managed in this setting [66]. Finally, simplification of prescribed treatment and of information provided to patients and carers following a TT assessment has the potential to reduce the carer burden and facilitate focus on the most relevant specific TTs [68].…”
Section: Resource Considerationsmentioning
confidence: 99%
“…Participants also recognised the impact that severe asthma has on family carers particularly when dealing with sudden severe attacks, but felt they were limited in providing care pathways. A needs assessment designed for carers of people with severe asthma is warranted to ensure their critical needs are met [ 67 ].…”
Section: Discussionmentioning
confidence: 99%